State of the Art and Development Trends of the Digital Radiography Systems for Cargo Inspection - Udod V. A. Viktor Anatolievich; Van J.; Osipov S. P. Sergey Pavlovich; Chakhlov S. V. Sergey Vladimirovich; Temnik A. K. Anatoly Konstantinovich (2016, 2016)
Title screen